2x+(8x-13)=47

Simple and best practice solution for 2x+(8x-13)=47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+(8x-13)=47 equation:


Simplifying
2x + (8x + -13) = 47

Reorder the terms:
2x + (-13 + 8x) = 47

Remove parenthesis around (-13 + 8x)
2x + -13 + 8x = 47

Reorder the terms:
-13 + 2x + 8x = 47

Combine like terms: 2x + 8x = 10x
-13 + 10x = 47

Solving
-13 + 10x = 47

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 10x = 47 + 13

Combine like terms: -13 + 13 = 0
0 + 10x = 47 + 13
10x = 47 + 13

Combine like terms: 47 + 13 = 60
10x = 60

Divide each side by '10'.
x = 6

Simplifying
x = 6

See similar equations:

| 5(2y)+4=4200 | | 2n-4n=16 | | 6x+6x=12x | | 27y+5y(7y-6)= | | 4y+5x=45c | | 4k^2-20k+9=0 | | 7x-(6x+8)=-4 | | 5(2y)+4=3360 | | 3z=16-19 | | 12x=180 | | -3y+7=-4y+2 | | -7.6-9y-6.5+4.7y= | | 0.05x+0.04y=168 | | 3n+18-n=38 | | -t=110 | | 6a=4-b | | 16x+4=20x^2+5x | | -2[9-(x+7)]= | | -8(3b+2)+(25b-4)=0 | | (5b)(-3a)= | | -8y-10x=44 | | 0=42x^2+13x-42 | | -0.3g-4.2+6.1g-0.9= | | x^2+57x=0 | | -4(N+9)= | | (y-5)-(y+2)=2y | | 0=30x^2+11x-30 | | 3x+(-12x)-5x= | | -12x+5x= | | 6w-10w=12 | | 3.2x-10=20.8 | | 3x+3+2= |

Equations solver categories